Implementasi Model Pembelajaran Picture and Picture dalam Meningkatkan Pengamalan Tata Cara Wudhu pada Siswa Kelas 5 di MI Miftahul Khoer - Mimin Rukmini; Muhamad Wildan Naufan; Apipah Sri Wahyuni; Imey Siti Sofiah; Mira Aryani (Departement of Mathematics Education, 2024)
This research aims to: First, implementexplain the implementation of the picture and picture learning model onin the material on understanding and practicing ablution procedures for grade 5 students at MI Miftahul Khoer. Second, Maximizingincreasing the understanding and practice of ablution procedures for grade 5 students at MI Miftahul Khoer. This research method is descriptive, namely field research using a qualitative approach. The subjects of this research consisted of all 28 grade 5 students. Data collection technique; The instruments ofin this research are observation, interviews and documentation which are then analyzed through four steps, namely: data collection, data reduction, data presentation and conclusion drawing. The research results showed that after applying the picture and picture learning model to the material on ablution procedures, there was quite a maximum improvement, the students were happy and interested in this learning model. As a result of the practice carried out, there were 18 students who were classified as able to carry out the ablution procedures properly and correctly, while the other 10 students were still not optimal. Factors that influence the occurrence of this problem are the lack of optimal learning process because teachers still apply conventional learning models so that students easily get bored in carrying out the learning process and the lack of student application of the understanding and practice of ablution procedures in everyday life.